Carbon Fiber Tape Material

The carbon fiber tape material, featuring integrated carbon fiber bundles and a thermoplastic resin fabric, addresses the issue of deformability and resin impregnation in the fiber placement method, resulting in improved productivity and mechanical strength of molded products.

JP7661725B2Active Publication Date: 2025-04-15TORAY INDUSTRIES INC
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021036955
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-09
Publication Date
2025-04-15
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

Existing carbon fiber tape materials used in the fiber placement method lack sufficient deformability, leading to challenges in mold followability and resin impregnation, which results in reduced productivity and lower carbon fiber content in molded products, thereby compromising mechanical strength.

Method used

A carbon fiber tape material is developed by integrating a group of carbon fiber bundles with a regular fabric, where the fabric is bonded to at least one side of the carbon fiber bundle via a binder. The fabric is composed of two thermoplastic resins with specific softening point relationships, and the tape material has a controlled weight and gap between carbon fiber bundles to enhance deformability and resin flow.

Benefits of technology

The carbon fiber tape material exhibits excellent mold followability and resin impregnation properties, increasing productivity in the fiber placement method and enabling the production of molded bodies with high carbon fiber content and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661725000002
    Figure 0007661725000002
  • Figure 0007661725000003
    Figure 0007661725000003
  • Figure 0007661725000004
    Figure 0007661725000004
Patent Text Reader

Abstract

To provide a carbon fiber tape material which has good followability to a mold and good impregnability with a matrix resin, enables improvement of productivity when reinforcing fiber laminate is produced by a fiber placement method, and enables acquisition of a molded body having a high carbon fiber content and high mechanical strength when impregnated with the resin and molded.SOLUTION: A carbon fiber tape material 100 is provided which is formed by integrating: a carbon-fiber-bundle group 102 in which a plurality of carbon fiber bundles 101 oriented in one direction are arranged; and a cloth 103 having regularity. The carbon fiber tape material satisfies (a) that the cloth is composed of at least two kinds of different thermoplastic resins and (b) that the basis weight of the tape material is in the range of 100 g / m2 to 400 g / m2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reinforcing fiber tape material, and a reinforcing fiber laminate and a molded article obtained by arranging and laminating the reinforcing fiber tape material. [Background technology]

[0002] Fiber-reinforced plastics (FRP), which are made of reinforcing fibers and resin, are used in aeronautics, space, and automotive applications due to their light weight and high strength. Examples of molding methods that achieve both productivity and high strength of FRP include resin-impregnated and cured resin laminates, such as resin transfer molding (RTM) and vacuum-assisted resin transfer molding (VaRTM). In the RTM molding method, a reinforced fiber laminate made of a reinforcing fiber base material composed of dry reinforcing fiber bundles that have not been pre-impregnated with matrix resin is placed in a mold, and a liquid low-viscosity matrix resin is injected to impregnate and solidify the matrix resin to form FRP. When particularly high productivity is required, a technique is used in which the cavity in the mold is made thicker than the final molded product thickness when injecting the resin, and the mold is closed to quickly impregnate the resin, thereby shortening the molding time of fiber-reinforced plastics. In recent years, a wet press molding method has also been used in which a liquid resin is applied to a reinforcing fiber laminate, the mold is then closed, and the resin is impregnated.

[0003] Reinforced fiber laminates to be impregnated and cured with resin have been conventionally formed by cutting out desired shapes from a reinforcing fiber substrate in a fixed width (i.e., approximately rectangular) fabric form composed of dry reinforcing fiber bundles in which the reinforcing fiber bundles are not impregnated with resin, such as woven fabrics or non-crimp fabrics (NCFs), shaping and fixing the cut pieces into a three-dimensional shape. However, when a desired shape is cut out from a fabric of a fixed width in this way, a large amount of scrap material is generated afterwards. In other words, the amount of reinforcing fiber waste increases, and there was a problem that the manufacturing cost is high in the conventional method of manufacturing a reinforcing fiber substrate in a fixed width fabric form in advance.

[0004] In response to these issues, the fiber placement method, in which reinforcing fiber bundles are placed only in the necessary places so that they are shaped to match the desired product shape, has attracted attention. According to the fiber placement method, the necessary amount of reinforcing fiber is placed in the necessary places, so the reinforcing fiber is made into a tape-like form and the tape material is placed only in the necessary places, which can significantly reduce the amount of reinforcing fiber that is discarded. Furthermore, the reinforcing fiber base material manufactured by the fiber placement method has less crimp and excellent straightness of the reinforcing fiber bundles compared to conventional woven fabrics and NCF, so the FRP obtained by injecting resin into it and curing it has high mechanical strength.

[0005] However, in the fiber placement method, when the carbon fiber tape is directly attached to the mold, the carbon fiber tape needs to follow the mold shape. Therefore, the wider the carbon fiber tape is and the more complex the mold shape is, the higher the deformability of the carbon fiber tape is required. In addition, high productivity is required in laminating the carbon fiber tape and in injecting the resin in RTM molding or VaRTM molding. Furthermore, the molded FRP is required to have a high carbon fiber content. If the carbon fiber content of the molded FRP is low, the ratio of carbon fiber to the volume of the component is low, which leads to a problem of reduced strength of the component.

[0006] As a conventional technique related to carbon fiber tape materials used in the fiber placement method, for example, Patent Document 1 proposes a carbon fiber tape material with a polymer adhesive bonded to both sides and a manufacturing method thereof. According to this method, a carbon fiber tape of a desired width can be manufactured with high accuracy by melting the polymer adhesive and attaching it to a group of reinforcing fiber bundles.

[0007] Patent Document 2 proposes a carbon fiber tape material in which a nonwoven veil is bonded to at least one side of a carbon fiber bundle, a preform, and a manufacturing method thereof. According to this method, by using a carbon fiber tape material to which a nonwoven veil is bonded, the effect of increasing the ease of resin diffusion in the in-plane direction during resin injection in RTM molding or VaRTM molding can be obtained. In addition, when a thermoplastic fiber material is used for the nonwoven veil, the resulting composite material can be toughened.

[0008] Furthermore, in Patent Document 3, the basis weight is 80 g / m 2 A reinforcing sheet material consisting of a knitted fabric of the following reinforcing fiber material and thermoplastic resin material has been proposed. With this configuration, by using a flexible knitted fabric, a sheet material can be obtained that maintains straightness even in a thin and wide state and does not deform, such as curling. In addition, because a thin knitted fabric with many voids is used, the air inside can be deaerated, and a molded product with few voids can be obtained.

[0009] Patent Document 4 proposes a multifilament reinforced yarn laminate in which a nonwoven fabric having two polymer components with different melting temperatures is used between and / or on the layers. With this configuration, when a preform is produced under heating using this laminate, some of the polymer melts between the layers, making the yarn slippery, and good drapeability is obtained. In addition, some of the polymer does not melt and retains its shape, so that good impregnation can be maintained in the subsequent impregnation step.

[0010] Furthermore, Patent Document 5 proposes a composite laminate impregnated with a thermosetting matrix resin, in which an intermediate layer in the laminate contains a soluble thermoplastic component that dissolves in the matrix resin and an insoluble component that does not dissolve in the matrix resin. According to this configuration, the soluble thermoplastic component that dissolves in the matrix resin of the intermediate layer is dissolved during curing, thereby making it possible to reduce the thickness of the intermediate layer and obtain an FRP molded product with a high carbon fiber content. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Special Publication No. 2012-510385 [Patent Document 2] Special Publication No. 2017-521291 [Patent Document 3] JP 2015-116806 A [Patent Document 4] Special Publication No. 2013-522078 [Patent Document 5] JP 2016-153213 A Summary of the Invention [Problem to be solved by the invention]

[0012] The invention of Patent Document 1 does not mention the deformability of the polymer adhesive. In addition, when a nonwoven veil is used as the polymer adhesive, the nonwoven veil is formed by randomly orienting short fibers, and therefore does not generally have sufficient deformability in the plane direction. Furthermore, when the polymer adhesive melts, the shape of the nonwoven veil is lost, and the deformability inherent to the fabric material is reduced.

[0013] The invention of Patent Document 2 uses a carbon fiber tape material in which a nonwoven veil is bonded to at least one side of a carbon fiber bundle. Therefore, as in the case of the cited document 1, the nonwoven veil is formed by randomly orienting short fibers, and therefore does not have sufficient deformability.

[0014] In the invention of Patent Document 3, a deformable fabric is used, but the basis weight of the reinforcing fiber material is low, and in order to obtain the desired product thickness, many sheet materials must be laminated, which makes the work complicated and reduces productivity. In addition, the invention described in Patent Document 3 relates to a reinforcing sheet material, and does not suggest the application of such a reinforcing sheet material to the fiber placement method.

[0015] In the invention of Patent Document 4, a nonwoven fabric having two polymer components with different melting temperatures is used between and / or on the layers as a laminate of multifilament reinforcing yarns, but the effect is to improve drapeability by melting the interlayer nonwoven fabric and acting as a lubricant when manufacturing a preform under heat, and is not intended to increase the reinforcing fiber content of the molded FRP panel. Also, as in Cited Document 1, the nonwoven veil is formed by randomly orienting short fibers, so it does not have sufficient deformability.

[0016] In the invention of Patent Document 5, the thickness of the intermediate layer can be reduced by dissolving a soluble thermoplastic component that dissolves in the matrix resin of the intermediate layer during curing, and an FRP molded product with a high carbon fiber content can be obtained. On the other hand, although films, particles, discontinuous filaments, and veils have been proposed as the material form used for the intermediate layer, intermediate layers in these forms cannot have sufficient deformation due to their structure, and fiber placement tapes or composite material laminates using such intermediate layers also do not have sufficient deformation.

[0017] The present invention solves the problems of the conventional techniques, specifically, it provides a carbon fiber tape material which has good mold conformability and matrix resin impregnation, can increase productivity when manufacturing a reinforced fiber laminate by a fiber placement method, and can provide a molded article having a high carbon fiber content and therefore high mechanical strength when impregnated with resin and molded. It also provides a reinforced fiber laminate and a molded article obtained from the carbon fiber tape material. [Means for solving the problem]

[0018] The present invention has been made to solve at least part of the above-mentioned problems, and is characterized by any one of the following configurations. (1) A carbon fiber tape material in which a group of carbon fiber bundles in which a plurality of carbon fiber bundles aligned in one direction are arranged is integrated with a fabric having regularity, The fabric is bonded to at least one surface of the carbon fiber bundle via a binder, thereby forming an integrated structure; A carbon fiber tape material characterized by satisfying the following (a) and (b). (a) the fabric is at least The thermoplastic resin is made of a first thermoplastic resin and a second thermoplastic resin, and the softening point T1 (°C) of the first thermoplastic resin and the softening point T2 (°C) of the second thermoplastic resin have the following relationship: 10 <T2-T1<120 (b) The carbon fiber tape material has a basis weight of 100 g / m 2 ~400g / m 2 Between ( 2 ) Fabric weight is 2g / m 2 ~30g / m 2 (1 ) The carbon fiber tape material described above. ( 3 ) A carbon fiber bundle having a gap of 0.1 mm to 1 mm between the bundles. ) or (2) The carbon fiber tape material described above. ( 4 ) The fabric and the binder are partially bonded to each other, 3 ) The carbon fiber tape material according to any one of the preceding claims. ( 5 (1) to (5) are fabrics each having a knitted structure, and the knitted structure is formed by positioning a first thermoplastic resin fiber made of a first thermoplastic resin and a second thermoplastic resin fiber made of a second thermoplastic resin according to a regularity. 4 ) The carbon fiber tape material according to any one of the preceding claims. ( 6(1) to (5) are fabrics in which a first thermoplastic resin fiber made of a first thermoplastic resin is used for the warp and a second thermoplastic resin fiber made of a second thermoplastic resin is used for the weft, or a first thermoplastic resin fiber made of a first thermoplastic resin is used for the weft and a second thermoplastic resin fiber made of a second thermoplastic resin is used for the warp. 4 ) The carbon fiber tape material according to any one of 。 Effect of the Invention

[0019] The carbon fiber tape material of the present invention has good mold conformability and resin impregnation properties, and when a reinforced fiber laminate is manufactured by a fiber placement method, its high deformability can increase productivity. Furthermore, when impregnated with resin and molded, a molded product having a high fiber content and mechanical strength can be provided. [Brief description of the drawings]

[0020] [Figure 1] 1 is a schematic diagram of a carbon fiber tape material according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram of another carbon fiber tape material according to the present invention. [Diagram 3] FIG. 2 is a schematic diagram of another carbon fiber tape material according to the present invention. [Figure 4] 1 is a schematic plan view of a fabric according to the present invention; [Diagram 5] 1 is a schematic plan view of a carbon fiber tape material using knitted fabric as a cloth according to the present invention. [Figure 6] FIG. 1 is a schematic plan view of a carbon fiber tape material using woven fabric for the fabric according to the present invention. [Figure 7] FIG. 2 is a schematic diagram showing a method for measuring fabric elongation. [Figure 8] FIG. 1 is a schematic diagram showing how the picture frame method is carried out using the two-side gripping method. [Figure 9] 1 is a graph showing the relationship between shear angle and tensile load when performing the picture frame method using the two-side gripping method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] FIG. 1 shows a schematic diagram of a carbon fiber tape material according to the present invention.

[0022] The carbon fiber tape material 100 shown in FIG. 1 is formed by integrating a plurality of carbon fiber bundles 101 aligned in one direction, a group of carbon fiber bundles 102 in which the carbon fiber bundles are arranged parallel (side by side) to each other in the width direction, and a fabric 103 having regularity.

[0023] The carbon fiber bundle used in the present invention may be, for example, a carbon fiber bundle that has been subjected to a sizing treatment in advance. By performing the sizing treatment, the bundling property of the carbon fiber bundle can be improved and the generation of fluff can be suppressed. In addition, the carbon fiber bundle used in the present invention may be a mixture of the carbon fiber and an organic fiber.

[0024] The number of filaments N (unit: K=1,000) of the carbon fiber bundle is preferably 1K (1,000) or more and 60K (60,000) or less. If the number of single fibers in the carbon fiber bundle 101 is less than 1K, the yarn width of the carbon fiber bundle 101 is narrow and defects such as twisting are likely to occur. If the number of single fibers in the carbon fiber bundle 101 is more than 60K, the carbon fiber weight per layer becomes high, and when the carbon fiber bundle 101 is aligned to form a substrate by a fiber placement method, the carbon fiber weight per layer becomes too high, which may narrow the tolerance range of the orientation design.

[0025] The carbon fiber tape material 100 has a structure in which a group of carbon fiber bundles, in which a plurality of carbon fiber bundles 101 aligned in one direction, are integrated with a regular fabric 103, thereby making it possible to increase the number of carbon fiber filaments and the weight per unit length of the carbon fiber tape material. In addition, when manufacturing fiber reinforced plastic by arranging and laminating the carbon fiber tape material by the fiber placement method, the time required to arrange and laminate the carbon fiber tape material to obtain a desired fiber volume content can be shortened, thereby improving productivity.

[0026] It is important that the fabric 103 is made of at least two kinds of thermoplastic resins. Here, the thermoplastic resin refers to thermoplastic resins such as polyamide resin, polyester resin, polyethylene terephthalate resin, polyvinyl formal resin, polyether sulfone resin, phenoxy resin, polycarbonate resin, etc., as well as thermoplastic elastomers (polystyrene-based resin, polyolefin-based resin, polyurethane-based resin, polyester-based resin, polyamide-based resin, polybutadiene-based resin, polyisoprene-based resin, fluorine-based resin, acrylonitrile-based resin, etc.), copolymers and modified bodies thereof, and resins obtained by blending two or more kinds of these resins. These resins can be made into fibers and shaped into woven fabric (woven fabric, knitted fabric) or nonwoven fabric, or into a film to make the fabric 103. By partially melting such fabric 103, it is integrated with the carbon fiber bundle group 102.

[0027] The carbon fiber tape material of the present invention has a fiber thickness of 100 g / m 2 ~400g / m 2 It is important that the weight of the carbon fiber tape is between 100g / m 2 If the thickness is smaller than this, when arranging the carbon fiber tape material by the fiber placement method, the number of carbon fiber tape materials to be laminated in order to obtain a laminate with a desired weight per unit area increases, and the time required for lamination increases, which becomes a constraint in further improving productivity. 2 If it is larger, the number of carbon fiber tape materials to be laminated in order to obtain a laminate with a desired basis weight becomes too small, and there is a risk that the degree of freedom in designing the fiber orientation will be narrowed. 2 ~300g / m 2 It is preferable that:

[0028] In one embodiment of the present invention, it is preferable that the fabric is composed of at least a first thermoplastic resin and a second thermoplastic resin, and that the softening point T1 (°C) of the first thermoplastic resin and the softening point T2 (°C) of the second thermoplastic resin have the following relationship: 10 <T2-T1<120

[0029] By maintaining this relationship, for example, by hardening at a temperature higher than T1 (℃) and lower than T2 (℃) during molding, the first thermoplastic resin can be melted to reduce the thickness of the molded product and obtain a CFRP molded product with a high carbon fiber content. The second thermoplastic resin does not melt, and acts as an interlaminar reinforcement in the molded product, contributing to improving the physical properties of the compression after impact (CAI) test.

[0030] In addition, in the placement process of the fiber placement method (also called the AFP method), for example, by placing while heating at a temperature higher than T1 (℃) and lower than T2 (℃), the first thermoplastic resin can be melted, reducing the thickness of the laminate, preventing the laminate from becoming bulky, and making it possible to manufacture a near-net-shape preform that matches the product dimensions. In addition, by performing heating and placement almost simultaneously, the first thermoplastic resin can be melted while the deformable tape is aligned with the mold shape, making it possible to form complex shapes.

[0031] The heating temperature during molding is preferably higher than T1 (°C) and lower than T2 (°C). By heating within this temperature range, the first thermoplastic resin hardens in a molten state, thereby reducing the thickness of the molded product, and the second thermoplastic resin does not melt, so that the second thermoplastic resin exists in the molded product and can act as an interlayer reinforcement, which contributes to improving the physical properties of the compression after impact (CAI) test.

[0032] In the present invention, it is preferable that the fabric 103 has a deformability. That is, in at least one direction of the fabric, the fabric elongation rate when a load of 80 mN / 50 mm is applied to the fabric is preferably 5% to 100%, and more preferably 15% to 100%. By using a deformable fabric, the deformability of the tape can be improved, and when directly attached to a mold by the fiber placement method, the carbon fiber tape can follow and fit the shape of the mold. If the fabric elongation rate is less than 5%, the fabric does not have sufficient deformability, and the carbon fiber tape cannot follow and fit the shape of the mold. If the fabric elongation rate is greater than 100%, the fabric will deform with a slight external force, making it difficult to attach the fabric to the carbon fiber with high precision and integrate it. Here, the fabric elongation rate is calculated according to the following formula in accordance with JIS L 1096 (2011 edition) 8.16.1. E p = [(L1-L0) / L0] x 100 E p : Fabric stretch rate (%) L0: Length of fabric between original marks (mm) L1: Fabric length when load is applied (mm)

[0033] The method for measuring the elongation rate of a fabric is shown in FIG. 7. FIG. 7(a) shows the state of fabric 703 before a constant load is applied. The fabric is cut to a specified size, a specified mark 711 is marked on the fabric, and the distance between the marks L0 is measured. Then, the fabric is chucked by clamp 710 as shown in FIG. 7(a). A load is then applied. FIG. 7(b) shows the state of fabric 703 after a constant load is applied. As shown in FIG. 7(b), by measuring the distance between the marks L1 after the constant load is applied, the elongation rate can be calculated from a specified formula. When measuring the elongation rate of a fabric from a tape material in which carbon fiber bundles and fabric are integrated, the fabric is peeled off from the tape material and then measured using the above procedure.

[0034] It is also important that the fabric 103 has regularity. In the present invention, "having regularity" means that a certain structure is continuously repeated in the longitudinal direction of the fabric (i.e., the longitudinal direction of the carbon fiber tape material). Examples of fabrics having regularity include knitted fabrics and woven fabrics. Since the structure of knitted fabrics and woven fabrics is continuously repeated in the longitudinal direction and the positions of the fibers are determined by the structure, it can be said that they are materials with little variation or bias in the fiber basis weight as fabrics. On the other hand, an example of a fabric that does not have regularity is nonwoven fabric (nonwoven veil). Since nonwoven fabrics are configured by randomly scattering short fibers and then bonding the fibers to each other, it is difficult to achieve the above-mentioned fabric elongation rate, and since the structure is not continuously repeated in the longitudinal direction, it is characterized in that the fiber orientation and basis weight are easily varied and biased.

[0035] Examples of the weave form of the fabric having regularity include weaves such as plain weave, twill weave, and satin weave, warp knitted structures such as denbi, cord, atlas, chain stitch, inlay, satin, half, and tulle, weft knitted structures, and combinations thereof.

[0036] These fabrics with regularity maintain their shape by knitting or weaving the fibers together. In other words, compared to nonwoven fabrics in which the fibers are bonded together and their relative positions are fixed, the positions of the knitted or woven fibers are not completely fixed and have a high degree of freedom, resulting in excellent deformability when force is applied in the plane (plane direction) of the fabric.

[0037] The fabric 103 has a basis weight of 2 g / m 2 Larger than 30g / m 2 Preferably, it is 4 g / m or less. 2 Larger than 20g / m 2 It is more preferable that the basis weight of the fabric 103 is 2 g / m or less. 2In the following cases, the fabric is easily torn, making it difficult to obtain the desired deformability. In addition, the fabric becomes thinner, making it difficult to ensure sufficient flow paths for the matrix resin during impregnation. Furthermore, because the fabric is thin, the thickness of the interlayer reinforcement in the molded product becomes thin, making it difficult to reinforce the interlayers of the laminated fiber bundles. On the other hand, when the basis weight of the fabric 103 is 30 g / m 2 If it is larger than , the thickness of the fabric becomes thicker, so the thickness of the carbon fiber tape material increases, and the thickness of the reinforced fiber laminate using the carbon fiber tape material is likely to be thicker than the desired product thickness, that is, it becomes difficult to make the reinforced fiber laminate using the carbon fiber tape material into a near net shape of the desired molded product. Also, the molded product molded using this reinforced fiber laminate is likely to have a large thickness of interlayer reinforcement, making it difficult to increase the fiber content (Vf:%) in the molded product.

[0038] Furthermore, the fabric 103 can be used not only to improve the deformability of the tape, but also to ensure a flow path for the matrix resin during resin impregnation and to strengthen the interlayer space by using a resin made of a highly tough material.

[0039] It is preferable that gaps 106 are provided between the multiple carbon fiber bundles 101 that constitute the carbon fiber tape material 100. By providing gaps 106 between the multiple carbon fiber bundles 101 that constitute the carbon fiber tape material 100, when the multiple carbon fiber bundles 101 are arranged in one direction by a fiber placement method to form a substrate, it is easy to ensure a flow path for the matrix resin. Even when multiple carbon fiber tape materials 100 are arranged in one direction without gaps by a fiber placement method to form a substrate, if gaps are provided between the multiple carbon fiber bundles 101 fixed within one carbon fiber tape material 100, it is easy to ensure the fluidity of the matrix resin during molding.

[0040] The gap 106 between the carbon fiber bundles is preferably 0.1 mm to 1 mm, and more preferably 0.2 mm to 0.8 mm. If the gap 106 is smaller than 0.1 mm, the flow path of the matrix resin becomes small, which may increase the time required for molding and lead to a decrease in productivity. If the gap 106 is larger than 1 mm, when the carbon fiber tape material is laminated by the fiber placement method to form a reinforced fiber laminate and molded, a part of the tape in the upper layer may fall into the gap between the carbon fiber bundles in the lower layer, which may reduce the straightness of the carbon fiber bundles. As a result, the compression properties of the obtained molded body may be reduced.

[0041] The tape width of the carbon fiber tape material 100 is preferably 2 mm to 2000 mm, and more preferably 5 mm to 100 mm. If the tape width of the carbon fiber tape material 100 is smaller than 2 mm, it becomes necessary to place more carbon fiber tape materials in the fiber placement process, and the productivity is likely to decrease. If the tape width of the carbon fiber tape material 100 is larger than 2000 mm, the device for manufacturing the tape becomes large, which is likely to lead to an increase in the tape cost, and is not preferable.

[0042] Carbon fiber tape material 200 shown in Fig. 2 is a schematic perspective view of another carbon fiber tape material according to the present invention. In this carbon fiber tape material 200, a fabric 203 having regularity is positioned on at least one side of a carbon fiber bundle group 202, as in the carbon fiber tape material shown in Fig. 1, but the fabric 203 is integrated with the carbon fiber bundle group 202 via a resin binder 204 attached to at least one side of the carbon fiber bundle group 202 for the purpose of maintaining the shape of each carbon fiber bundle 201. In other respects, it has the same configuration as the carbon fiber tape material 100 shown in Fig. 1. The resin binder 204 may be in the form of particles or non-woven fabric, but is not limited to these forms and may also be a film, mesh, emulsion, coating, or auxiliary thread wound around the carbon fiber bundle.

[0043] Examples of materials that can be used for the resin binder include thermoplastic resins such as polyamide resin, polyester resin, polyethylene terephthalate resin, polyvinyl formal resin, polyethersulfone resin, phenoxy resin, and polycarbonate resin, as well as other phenolic resins, phenoxy resins, and epoxy resins, as well as thermoplastic elastomers such as polystyrene resins, polyolefin resins, polyurethane resins, polyester resins, polyamide resins, polybutadiene resins, polyisoprene resins, fluorine resins, and acrylonitrile resins, as well as copolymers, modified products, and resins that are blends of two or more of these resins.

[0044] These resin binders not only serve the adhesive function of bonding layers together when the composite is made into a reinforced fiber laminate, but can also be used to ensure flow paths for the matrix resin during resin impregnation and to strengthen the interlayer spaces by using resins with high toughness.

[0045] The carbon fiber bundle 201 may be fixed by the resin binder 204 in such a manner that the resin binder 204 is visibly attached to or partially impregnated on the surface of the carbon fiber bundle 201 to bind the filaments contained in the carbon fiber bundle, or the resin binder 204 may be impregnated inside the carbon fiber bundle 201 so as not to be visible from the surface to bind the filaments contained in the carbon fiber bundle to each other. In addition, the resin binder may be wound around the carbon fiber bundle 201, or the carbon fiber bundle 201 may be covered with the resin binder.

[0046] The amount of the resin binder required to fix the carbon fiber bundles 201 is preferably 25 wt% or less, more preferably 20 wt% or less, and even more preferably 15 wt% or less, based on the weight of the carbon fiber bundles 201. If the amount of the resin binder is greater than 25 wt%, when the tape material is arranged and laminated by a fiber placement method to form a reinforced fiber laminate and molded, the viscosity of the matrix resin increases and the flowability is likely to decrease, which tends to reduce productivity. In addition, since it takes a long time for the matrix resin to flow, the viscosity of the matrix resin increases further, which tends to generate resin-unimpregnated portions in the molded body, leading to deterioration of the mechanical properties of the molded body.

[0047] The softening point Ts (°C) of the fabric 203 is preferably higher than that of the resin binder 204. Here, when the fabric 203 is made of a plurality of types of thermoplastic resins, the softening point of the thermoplastic resin with the lowest softening point among the plurality of types of thermoplastic resins is regarded as the softening point Ts (°C) of the fabric 203. For example, when only two types of thermoplastic resins, a first thermoplastic resin and a second thermoplastic resin, are used, the softening point Ts (°C) of the fabric 203 coincides with the softening point T1 (°C) of the first thermoplastic resin. At this time, by heating and pressing at a temperature higher than the softening point of the resin binder 204 and lower than the softening point of the fabric 203, the fabric 203 and the carbon fiber bundle group 202 can be integrated with each other using the molten resin binder 204 as an adhesive. In this case, the fabric 203 does not melt and retains the shape of the structure, so that a carbon fiber tape material 200 with excellent deformability can be obtained without impairing the deformability of the fabric 203.

[0048] Moreover, the resin binder 204 preferably has a softening point (°C) higher than 40°C and lower than the softening point Ts (°C) of the fabric 203. By using such a resin binder, when the viscosity is reduced by heating and then the temperature is returned to normal temperature by cooling or the like, the filaments constituting the carbon fiber bundle are fixed to each other, and a certain shape can be more reliably maintained as a carbon fiber bundle. When the shape of the carbon fiber bundle is maintained constant, the carbon fiber tape material 200 is placed on a mold by the fiber placement method, and when pressure or tension is applied to the carbon fiber tape material 200, the shape of the carbon fiber bundle can be suppressed from collapsing. As a result, the gaps 206 provided between the carbon fiber bundles 201 can be maintained without being crushed, and the flow path of the matrix resin during molding can be more reliably secured.

[0049] In this specification, the term "softening point" refers to the temperature at which a resin material, such as a fabric or a resin binder, softens / melts when the resin material reaches a temperature equal to or higher than that temperature. Specifically, when the resin material is a crystalline polymer, it refers to the melting point, and when the resin material is an amorphous polymer, it refers to the glass transition point.

[0050] In addition, the carbon fiber tape material according to the present invention is preferably integrated by bonding the fabric to at least one side of the carbon fiber bundles via a binder. In the schematic perspective view of the carbon fiber tape material 300 shown in Fig. 3, a fabric 303 having regularity is arranged on at least one side (both sides in Fig. 3) of a carbon fiber bundle group 302 in which a plurality of carbon fiber bundles 301 are arranged in parallel, as in the embodiment of Fig. 2. The fabric 303 is integrated with the carbon fiber bundle group 302 via a resin binder 304 attached to the surface of the carbon fiber bundle group 302 for the purpose of maintaining the shape of each carbon fiber bundle 301.

[0051] Further, in the carbon fiber tape material according to the present invention, it is preferable that the base and the binder are partially bonded. As an example of partial bonding, in the embodiment shown in FIG. 3, among the resin binders 304 provided on the surface of the carbon fiber bundle group 302, only the resin binders 304 in the region surrounded by the bonding region 305 are melted to contribute to the bonding between the fabric 303 and the carbon fiber bundle group 302. The bonding region 305 is formed not continuously but discretely (intermittently) in the fiber orientation direction of the carbon fiber bundles 301 in at least a part of the carbon fiber tape material 300. Here, the "bonding region" refers to a region where the fabric 303 and the carbon fiber bundle group 302 are bonded to each other via the resin binder 304. The fabric 303 and the carbon fiber bundle group 302 are integrated with each other by bonding at least a part of the bonding region, and the form of the carbon fiber tape material can be maintained. The carbon fiber tape material 300 shown in FIG. 3 has the same configuration as the carbon fiber tape material 200 shown in FIG. 2 except for the above points.

[0052] In the present invention, it is preferable that the adhesive regions 305 are formed discretely in the fiber orientation direction of the carbon fiber bundles 301 as described above. When the adhesive regions 305 extend over the entire tape and the carbon fiber bundles 302 and the fabric 303 are adhered over the entire tape surface, the thermoplastic fibers constituting the fabric are completely fixed in position by adhesion to the carbon fiber bundles, and the inherent deformability of the fabric is reduced. In Fig. 3, the adhesive regions 305 are discretely distributed in the fiber orientation direction, leaving room for the fabric to move freely locally, and thus the reduction in the deformability of the fabric due to adhesion can be suppressed.

[0053] 4 shows a schematic plan view of a fabric according to the present invention. In this embodiment, a warp knit fabric with chain stitches and inlays is used as the fabric 403, and this knit fabric is composed of a chain portion 406 and an insert portion 407. In the present invention, it is important that the fabric is composed of at least two different thermoplastic resins. In one example of this embodiment, the chain portion 406 is composed of a first thermoplastic resin 408, and the insert portion 407 is composed of a second thermoplastic resin 409.

[0054] FIG. 5 is a schematic plan view of a carbon fiber tape material using the knitted fabric shown in FIG. 4 as the fabric. In order to explain the concept of the present invention, FIG. 5(a) shows the carbon fiber tape material before molding, and FIG. 5(b) shows the carbon fiber tape molded product after resin is impregnated and molded. In FIG. 5(a), a knitted fabric formed by using a first thermoplastic resin 508 as a chain part and a second thermoplastic resin 509 as an insertion part is attached to a carbon fiber group 502 and integrated to form a carbon fiber tape material 500. Here, the first thermoplastic resin 508 is melted as shown in FIG. 5(b) by hardening and molding at a hardening temperature higher than the softening point T1 of the first thermoplastic resin 508 and lower than the softening point T2 of the second thermoplastic resin 509. As a result, the bulk occupied by the first thermoplastic resin 508 before melting is reduced, and a molded product with a reduced thickness, that is, a molded product with a high carbon fiber occupancy rate, is obtained.

[0055] Here, it is preferable that the first thermoplastic resin fibers made of the first thermoplastic resin 508 and the second thermoplastic resin fibers made of the second thermoplastic resin 509 are each positioned according to a regularity. In the fabric after molding, only the second thermoplastic resin fibers remain in the form, but since the first thermoplastic resin fibers and the second thermoplastic resin fibers are each arranged according to a regularity, in the fabric after molding, the second thermoplastic resin fibers are regularly arranged on the tape, so that a uniform molded product can be obtained with little variation in interlayer toughness depending on the part of the molded product.

[0056] The arrangement of the first thermoplastic resin fiber and the second thermoplastic resin fiber is not limited to a specific location. For example, in this embodiment, the first thermoplastic resin 508 may be used in the insertion portion, and the second thermoplastic resin 509 may be used in the chain portion. In addition to the warp knitted fabric with chain stitch and inlay (insertion), the first thermoplastic resin 508 may be used in any location of the warp knitted fabric, weft knitted fabric, woven fabric, and other fabric forms, such as chain stitch and half fabric or tulle fabric.

[0057] FIG. 6 is a schematic plan view of a carbon fiber tape material using a plain weave fabric as the fabric. As in FIG. 5, FIG. 6(a) shows the carbon fiber tape material before molding, and FIG. 6(b) shows the carbon fiber tape molded product after resin is impregnated and molded. In FIG. 6(a), a plain weave fabric made of a first thermoplastic resin 608 as the warp and a second thermoplastic resin 609 as the weft is attached to a carbon fiber group 602 and integrated to form a carbon fiber tape material 600. Here, the first thermoplastic resin 608 is melted as shown in FIG. 6(b) by hardening and molding at a hardening temperature higher than the softening point T1 of the first thermoplastic resin 608 and lower than the softening point T2 of the second thermoplastic resin 609. As a result, the bulk occupied by the first thermoplastic resin 608 before melting is reduced, and a molded product with a reduced thickness, that is, a molded product with a high carbon fiber occupancy rate, is obtained.

[0058] The carbon fiber tape material according to the present invention having the above-mentioned configuration can exhibit the following shear deformation performance: That is, the tensile load F [N] measured at a shear angle θ [°] in the range of 0° to 45° using the picture frame method with two-side gripping does not have a maximum value of the tensile load F [N] when the shear angle θ [°] is in the range of 0° to 1.0°, the maximum value of the tensile load F [N] measured at a shear angle θ [°] in the range of 0° to 45° is greater than 0.5 [N], and ΔF / Δθ is greater than 0.1 and smaller than 1.0 when θ [°] is in the range of 0.1° to 1.0°.

[0059] The picture frame method using the two-side gripping method, which is a method for evaluating shear deformation performance, will be described. Figure 8 shows a schematic diagram of the picture frame method using the two-side gripping method. One or more carbon fiber tape materials 800 with a length of 220 mm are arranged in parallel without any gaps, and prepared so that the sum of the overall width is 150 mm. After marking the gripping portion 813 so that the gripping distance is 200 mm, the carbon fiber tape material 800 is attached to the picture frame jig 815 so that the two sides at both ends of the carbon fiber tape are gripped, so that the gripping portion 813 is 200 mm, the measurement angle α [°] is 90°, and the longitudinal direction of the carbon fiber tape is parallel to the two sides 814 of the picture frame that are not gripping the carbon fiber tape material. After attaching a picture frame jig to a universal testing machine (not shown) so that the measurement angle α [°] is 90°, the picture frame jig is pulled vertically at a speed of 50 mm / min, and the tensile force F [N] and measurement angle α are measured. After that, the shear angle θ [°] calculated from the following formula, and ΔF / Δθ when θ [°] is between 0.1° and 1.0° are calculated. θ[°]=90°―α[°]

[0060] An example of a shear angle-tensile load graph when the picture frame method using the two-side gripping method was performed on the carbon fiber tape material according to the present invention is shown in Figure 9. Figure 9(a) is a shear angle-tensile load graph when testing shear angles θ [°] from 0 to 45, and Figure 9(b) is a graph enlarging the vicinity of the shear angle θ [°] from 0 to 1 on the same graph.

[0061] In the carbon fiber tape material according to the present invention, when the shear angle θ [°] is tested from 0° to 45°, it is preferable that the tensile load F does not have a maximum value when the shear angle θ [°] is between 0° and 1.0°. When the maximum value of the tensile load F [N] is between the shear angle θ [°] of 0° and 1.0°, it means that the carbon fiber tape material cannot maintain its shape and collapses before the shear angle θ [°] reaches 1.0°. In this case, the value of ΔF / Δθ cannot be evaluated as the shear deformation performance of the carbon fiber tape material.

[0062] In the carbon fiber tape material according to the present invention, when the tensile load F does not have a maximum value between the shear angle θ [°] of 0° and 1.0°, ΔF / Δθ between the shear angle θ [°] of 0.1° and 1.0° is preferably smaller than 1.0, more preferably smaller than 0.4, and even more preferably smaller than 0.2. When ΔF / Δθ is 1.0 or more, a large force is required to shear-deform the carbon fiber tape material, and good mold-following property cannot be obtained when the carbon fiber tape material is aligned and placed in a mold by the fiber placement method. On the other hand, ΔF / Δθ is preferably larger than 0.1. When ΔF / Δθ is 0.1 or less, the carbon fiber tape material undergoes large shear deformation with the application of a small force, and the stability of the carbon fiber tape material is impaired.

[0063] When the carbon fiber tape material according to the present invention is tested with the shear angle θ [°] ranging from 0° to 45°, the maximum value of the tensile load F is preferably greater than 0.5 N, and more preferably greater than 1.0 N. When the carbon fiber tape material is tested with the shear angle θ [°] ranging from 0° to 45°, if the maximum value of the tensile load F is 0.5 N or less, the carbon fiber bundles and the cloth material will peel off from each other, and the carbon fiber tape material will not be able to maintain the tape form.

[0064] The carbon fiber tape material of the present invention is used in a reinforced fiber laminate. The reinforced fiber laminate is obtained by arranging and stacking the carbon fiber tape material of the present invention and fixing at least a part between the layers, thereby maintaining the shape. By adopting such a configuration, the gap between the carbon fiber bundles constituting the reinforced fiber laminate can be set to any distance. As a result, the fluidity of the matrix resin during molding can be ensured, and the productivity can be improved by expanding the type of resin to be injected and the width of the process window.

[0065] In addition, it is preferable to impregnate the reinforced fiber laminate using the carbon fiber tape material with a matrix resin to form a fiber reinforced resin molded product. By adopting the above-mentioned configuration, the fiber reinforced resin molded product obtained is completely impregnated with resin to the inside, and has high mechanical properties. EXAMPLES

[0066] The carbon fiber tape material according to the present invention will be described based on examples. Table 1 shows the conditions and results of the examples and comparative examples.

[0067] Example 1 <Reinforced fiber bundle> As the reinforcing fiber bundle, a carbon fiber "TORAYCA" (registered trademark) T800SC manufactured by Toray Industries, Inc., which had been subjected to a sizing treatment in advance, and had 24,000 carbon fiber filaments (N=24K) was used.

[0068] <Fabric> The fabric used was a regular knitted fabric (material: polyamide, basis weight: 6g / m2) that was warp knitted using a tricot machine with chain stitches and inlays. 2 ) was used.

[0069] <Measurement of fabric stretch rate> The elongation of the fabric was measured as follows, with reference to JIS L 1096 8.16.1. That is, the fabric was cut to a width of 50 mm and a length of 300 mm so that the wale direction of the fabric was the longitudinal direction, and marks were made on the gripping parts so that the gripping distance was 200 mm. After fixing one end of the test piece with a clamp, a load of 80 mN / 50 mm was gently applied and held for 1 minute, and the length between the marks was measured. The fabric elongation was calculated from the following formula, and the elongation was 48%. E p = [(L1-L0) / L0] x 100 E p : Fabric stretch rate (%) L0: Length of fabric between original marks (mm) L1: Fabric length when load is applied (mm)

[0070] <Carbon fiber tape material> Using a carbon fiber bundle manufacturing device (not shown), one carbon fiber bundle was pulled out from a bobbin, and the width was narrowed without slitting while adjusting the thickness, and then heat-meltable binder particles (average particle size: 0.2 mm) with a softening point temperature of 80° C. were sprayed onto the surface of the carbon fiber bundle. The binder particles were sprayed so that the weight ratio was 5% (the weight of the obtained carbon fiber bundle was taken as 100%), and then the binder particles were melted and cooled to obtain a carbon fiber bundle with a thread width of 4.8 mm whose shape was fixed.

[0071] Ten carbon fiber bundles were aligned in parallel in the longitudinal direction, and then a knitted fabric (cloth) with a first thermoplastic resin (material: polyamide) having a softening point temperature T1 (°C) of 110°C and a second thermoplastic resin (material: polyamide) having a softening point temperature T2 (°C) of 200°C was placed on one side of the carbon fiber bundle, and heated at 90°C to melt the binder particles, thereby partially bonding and integrating the knitted fabric and carbon fiber bundles via the binder particles as shown in Figure 3. This resulted in a tape material with a width of 50 mm and a basis weight of 212 g / m 2 Thus, a carbon fiber tape material was obtained in which the gap between each of the carbon fiber bundles was 0.2 mm.

[0072] <Deformability of carbon fiber tape material> The picture frame method using the two-side gripping method was carried out to evaluate the deformability of the carbon fiber tape material. Three carbon fiber tape materials with a length of 220 mm and a width of 50 mm were arranged in parallel, and marks were made on the gripping parts so that the gripping interval was 200 mm. Then, the three carbon fiber tape materials arranged in parallel were attached to the picture frame jig shown in FIG. 8 so that the gripping part was 200 mm and the measurement angle α [°] was 90°, and the measurement was carried out by attaching it to grip two sides. As a result, the tensile load F [N] in the range of shear angle θ [°] from 0° to 45° was greater than 0.5 [N] at the maximum value, and the maximum value did not exist between shear angle θ [°] of 0° and 1.0°. Then, ΔF / Δθ=0.22 was obtained, and it was confirmed that the carbon fiber tape material exhibited good deformability against the in-plane shear force.

[0073] <Reinforced fiber laminate> Using a fiber placement device (not shown), the carbon fiber tape material obtained as described above was arranged on a stand in one direction so that a gap of 0.7 mm was provided between each carbon fiber tape material, and the carbon fiber tape material was cut and arranged repeatedly to form a 300 mm x 300 mm square shape to produce a sheet substrate. Adjacent carbon fiber tape materials were overlapped by 1 mm with the adjacent knitted fabrics, and the overlapped portion was heated at 100°C to bond and integrate the sheets.

[0074] The obtained sheet substrate was placed in a pyramid (tetrahedron) shaped mold (base: equilateral triangle with sides of 14 cm, height: 7 cm), and the upper mold was lowered while applying tension to the sheet substrate to press-form it, after which the lower mold was heated at 100°C for 10 minutes. As a result, the sheet substrate showed good formability without any major wrinkles. Using the same procedure, the sheet substrate was molded layer by layer in the pyramid shaped mold, after which the upper mold was closed and the lower mold was heated at 100°C for 10 minutes. As a result, a good reinforced fiber laminate was obtained without any major wrinkles.

[0075] <Molded body> The obtained reinforced fiber laminate was placed in the pyramid-shaped lower mold described above, vacuum-bagged using a bag film, and then the mold was placed in an oven with an atmospheric temperature of 100°C. Then, matrix resin (epoxy resin) was injected and cured in an atmosphere of 170°C. As a result, the carbon fiber content of the molded product was 59%, and a good molded product with a high carbon fiber content and no resin-impregnated areas was obtained. As a result of carrying out CAI (compression after impact test) using this molded product, good results with excellent impact resistance were obtained. Table 1 shows the CAI ratios of each Example and Comparative Example, where the value of this test result is 100.

[0076] Example 2 A carbon fiber tape was obtained in the same manner as in Example 1 except for the following points. The fabric is a regular knitted fabric (material: polyamide, basis weight: 6g / m2) warp-knitted in a chain + half structure using a tricot machine. 2 ) was used. The fabric used was a knitted fabric in which the first thermoplastic resin had a softening point temperature T1 (℃) of 160℃ and the second thermoplastic resin had a softening point temperature T2 (℃) of 180℃.

[0077] <Measurement of fabric stretch rate> The elongation was measured in the same manner as in Example 1, and the elongation in the wale direction was found to be 35%.

[0078] <Deformability of carbon fiber tape material> As a result of carrying out the picture frame method by the two-side gripping method in the same manner as in Example 1, the maximum tensile load F [N] was greater than 0.5 [N] when the shear angle θ [°] was in the range of 0° to 45°, and the maximum value did not exist when the shear angle θ [°] was in the range of 0° to 1.0°. In addition, ΔF / Δθ was 0.36, and it was confirmed that the carbon fiber tape material exhibited good deformability against the in-plane shear force.

[0079] <Reinforced fiber laminate> As a result of carrying out the same method as in Example 1, a good reinforcing fiber laminate was obtained without any twisting or wrinkling of the sheet substrate.

[0080] <Molded body> As a result of carrying out the same method as in Example 1, the carbon fiber content of the molded product was 57%, and a good molded product with a high carbon fiber content and no unimpregnated areas was obtained. CAI (compression after impact) was carried out using this molded product, and when converted to the nominal carbon fiber content of Example 1, the CAI ratio was 105, and good results with excellent impact resistance were obtained.

[0081] Example 3 A carbon fiber tape was obtained in the same manner as in Example 1 except for the following points. - As a fabric, plain weave fabric (warp and weft material: polyamide, basis weight: 6g / m 2 , fiber orientation: ±45°) was used. The fabric used was a woven material with a first thermoplastic resin having a softening point temperature T1 (℃) of 130℃ and a second thermoplastic resin having a softening point temperature T2 (℃) of 200℃.

[0082] <Measurement of fabric stretch rate> The elongation was measured in the same manner as in Example 1, and the elongation in the wale direction was found to be 55%.

[0083] <Deformability of carbon fiber tape material> As a result of carrying out the picture frame method by the two-side gripping method in the same manner as in Example 1, the maximum tensile load F [N] was greater than 0.5 [N] when the shear angle θ [°] was in the range of 0° to 45°, and the maximum value did not exist when the shear angle θ [°] was in the range of 0° to 1.0°. In addition, ΔF / Δθ was 0.19, and it was confirmed that the carbon fiber tape material exhibited good deformability against the in-plane shear force.

[0084] <Reinforced fiber laminate> As a result of carrying out the same method as in Example 1, a good reinforcing fiber laminate was obtained without any twisting or wrinkling of the sheet substrate.

[0085] <Molded body> As a result of carrying out the same method as in Example 1, the carbon fiber content of the molded product was 60%, and a good molded product with a high carbon fiber content and no unimpregnated areas was obtained. CAI (compression after impact) was carried out using this molded product, and the CAI ratio was 97 when converted to the nominal carbon fiber content of Example 1, and a good result with excellent impact resistance was obtained.

[0086] Comparative Example 1 A carbon fiber tape was obtained in the same manner as in Example 1 except for the following points. -One type of thermoplastic fiber (material: polyamide, basis weight: 6g / m 2 ) and a knitted fabric with a chain + inlay structure with a softening point of 200°C was used.

[0087] <Measurement of fabric stretch rate> The elongation was measured in the same manner as in Example 1, and the elongation in the wale direction was 51%.

[0088] <Deformability of carbon fiber tape material> As a result of carrying out the picture frame method by the two-side gripping method in the same manner as in Example 1, the maximum tensile load F [N] was greater than 0.5 [N] when the shear angle θ [°] was in the range of 0° to 45°, and the maximum value did not exist when the shear angle θ [°] was in the range of 0° to 1.0°. In addition, ΔF / Δθ was 0.24, and it was confirmed that the carbon fiber tape material exhibited good deformability against the in-plane shear force.

[0089] <Reinforced fiber laminate> As a result of carrying out the same method as in Example 1, a good reinforcing fiber laminate was obtained without any twisting or wrinkling of the sheet substrate.

[0090] <Molded body> As a result of carrying out the same method as in Example 1, the carbon fiber content of the molded product was 47%, and although there were no areas not impregnated with resin, the molded product had a low carbon fiber content.

[0091] Comparative Example 2 A carbon fiber tape was obtained in the same manner as in Example 1 except for the following points. -One type of thermoplastic fiber (material: polyamide, basis weight: 6g / m 2 ) and had a softening point of 130°C.

[0092] <Measurement of fabric stretch rate> The elongation was measured in the same manner as in Example 1, and the elongation in the wale direction was found to be 8%.

[0093] <Deformability of carbon fiber tape material> As a result of carrying out the picture frame method by the two-side gripping method in the same manner as in Example 1, the maximum tensile load F [N] was greater than 0.5 [N] when the shear angle θ [°] was in the range of 0° to 45°, and the maximum value did not exist when the shear angle θ [°] was in the range of 0° to 1.0°. In addition, ΔF / Δθ was 1.16, and it was confirmed that the carbon fiber tape material had poor deformability against the in-plane shear force.

[0094] <Reinforced fiber laminate> As a result of carrying out the same method as in Example 1, it was confirmed that the sheet substrate had kinks in multiple locations in the reinforcing fiber laminate.

[0095] <Molded body> As a result of carrying out the same method as in Example 1, the carbon fiber content of the molded product was 58%, and a molded product with a high carbon fiber content was obtained. CAI (compression after impact test) was carried out using this molded product, and as a result of converting it to the nominal carbon fiber content of Example 1, the CAI ratio was 78, resulting in poor impact resistance.

[0096] [Table 1] [Industrial Applicability]

[0097] The carbon fiber tape material of the present invention and the reinforced fiber laminate using the same have excellent impregnation properties with matrix resins, and therefore, a molded article obtained using such a reinforced fiber laminate is particularly suitable for use in large components for aircraft, automobiles, ships, etc., and components for general industrial applications such as wind turbine blades. [Explanation of symbols]

[0098] 100, 200, 300, 500, 600, 800 Carbon fiber tape material 101, 201, 301, 501, 601 Carbon fiber bundle 102, 202, 302, 502, 602 Carbon fiber bundles 103, 203, 303, 403, 503, 603, 703 Fabric 106, 206, 306 Gap 204, 304 Resin binder 305 Adhesive area 406 Chain part 407 Insertion part 408, 508, 608 First thermoplastic resin 409, 509, 609 Second Thermoplastic Resin 710 Clamp 711 mark 813 Grip part 814 Two sides not holding the carbon fiber tape material 815 Picture Frame Jig

Claims

1. A carbon fiber tape material comprising a group of carbon fiber bundles, each of which is an array of carbon fiber bundles aligned in one direction, and a fabric having a regularity, the carbon fiber bundles being integrated together by the fabric being adhered to at least one side of the carbon fiber bundles via a binder, and the carbon fiber tape material being characterized in that the following (a) and (b) are satisfied: (a) The fabric is composed of at least a first thermoplastic resin and a second thermoplastic resin, and the softening point T1 (°C) of the first thermoplastic resin and the softening point T2 (°C) of the second thermoplastic resin have the following relationship: 10<T2-T1<120 (b) The carbon fiber tape material has a basis weight of 100 g / m 2 Up to 400 g / m 2 Between

2. The fabric has a basis weight of 2 g / m 2 ~30g / m 2 The carbon fiber tape material according to claim 1, characterized in that

3. The carbon fiber tape material according to claim 1 or 2, characterized in that there are gaps of 0.1 mm to 1 mm between the carbon fiber bundles.

4. The carbon fiber tape material according to any one of claims 1 to 3, wherein the fabric and the binder are partially bonded to each other.

5. The carbon fiber tape material according to any one of claims 1 to 4, wherein the fabric is a knitted fabric, and the first thermoplastic resin fiber made of the first thermoplastic resin and the second thermoplastic resin fiber made of the second thermoplastic resin are positioned according to a regularity to form the knitted fabric.

6. The carbon fiber tape material according to any one of claims 1 to 4, wherein the fabric is woven, and a first thermoplastic resin fiber made of a first thermoplastic resin is used for the warp yarn and a second thermoplastic resin fiber made of a second thermoplastic resin is used for the weft yarn, or a first thermoplastic resin fiber made of a first thermoplastic resin is used for the weft yarn and a second thermoplastic resin fiber made of a second thermoplastic resin is used for the warp yarn.

Citation Information

Patent Citations

  • Reinforcing fiber sheet

    JP1999077869A

  • Composite reinforced fiber base and preform

    JP2002113802A

  • Reinforcing mesh fabric and method for reinforcing material

    JP2002194640A

  • Reinforcing fiber sheet

    JP2008007871A

  • Novel intermediate material with a certain width for the manufacture of composite material parts by direct method

    JP2012510385A